The management of upper respiratory tract infections - Teng, C.L.; Shajahan, Y.; Khoo, Ee Ming; Nurjahan, I.; Leong, K.C.; Yap, T.G. (Malaysian Medical Association, 2001)
Upper respiratory tract infections are the commonest reason for consultation in primary care. Group A Î²-haemolytic Streptococcus (GABHS), the most important bacterial pathogen in this condition, can be cultured from about 300 of patients, more so in children than adults. Clinical features that are predictive of positive GABHS culture are absence of cough, fever, cervical adenopathy, tonsillar enlargement and tonsillar exudate. Use of a sore throat score can help in the detection of streptococcal throat infection. Symptomatic therapies which are useful include anticholinergic, antihistamine, decongestant, humified hot air and Vitamin C. Antibiotics are universally over-prescribed in this condition as a result of high patient expectation and faulty clinical decision making. Oral Penicillin V for 10 days is the drug of choice. Effective intervention to reduce inappropriate antibiotic prescription probably require a multi-faceted approach targeted at both the patients and the prescribers.